Timah dalam Pembentukkan Budaya dan Ekonomi Masyarakat Bangka - ‘Ulya, Inarotul; Amilda, Amilda; Otoman, Otoman (Program Studi Sejarah Peradaban Islamm UIN Raden Fatah Palembang, 2024)
This research begins with the assumption that the tin policy during the Palembang- Independence Sultanate had an influence on the cultural and economic formation of the Bangka people. This research is a library research using a historical approach. Primary data used in this research was obtained from the PT, Timah Tbk Museum Archives in Pangkalpinang. The theory used in this research is the theory of historical materialism by Karl Marx. The results of this research show that the existence of policies on tin mining from the time of the Palembang Sultanate until independence had a direct impact on the people of Bangka who could not access natural tin resources because they were controlled by tin rulers. The existence of tin mining activities then contributed to the formation of culture and economic changes in the people of Bangka.